Glutathione levels and activities of glutathione metabolism enzymes in patients with schizophrenia: A systematic review and meta-analysis. (October 2019) - Tsugawa, Sakiko; Noda, Yoshihiro; Tarumi, Ryosuke; Mimura, Yu; Yoshida, Kazunari; Iwata, Yusuke; Elsalhy, Muhammad; Kuromiya, Minori; Kurose, Shin; Masuda, Fumi; Morita, Shinji; Ogyu, Kamiyu; et al.
Background: Glutathione is among the important antioxidants to prevent oxidative stress. However, the relationships between abnormality in the glutathione system and pathophysiology of schizophrenia remain uncertain due to inconsistent findings on glutathione levels and/or glutathione-related enzyme activities in patients with schizophrenia. Methods: A systematic literature search was conducted using Embase, Medline, PsycINFO, and PubMed. Original studies, in which three metabolite levels (glutathione, glutathione disulfide, and total glutathione (glutathione+glutathione disulfide)) and five enzyme activities (glutathione peroxidase, glutathione reductase, glutamate-cysteine ligase, glutathione synthetase, and glutathione S-transferase) were measured with any techniques in both patients with schizophrenia and healthy controls, were included. Standardized mean differences were calculated to determine the group differences in the glutathione levels with a random-effects model. Results: We identified 41, 9, 15, 38, and seven studies which examined glutathione, glutathione disulfide, total glutathione, glutathione peroxidase, and glutathione reductase, respectively. Patients with schizophrenia had lower levels of both glutathione and total glutathione and decreased activity of glutathione peroxidase compared to controls. Glutathione levels were lower in unmedicated patients with schizophrenia than those in controls while glutathione levels did not differ between patients with first-episode psychosis and controls. Conclusions: Our findings suggested that there may be glutathione deficits and abnormalities in the glutathione redox cycle in patients with schizophrenia. However, given the small number of studies examined the entire glutathione system, further studies are needed to elucidate a better understanding of disrupted glutathione function in schizophrenia, which may pave the way for the development of novel therapeutic strategies in this disorder.